Research Themes and Trends in Health Information Systems - Raghupathi, W.; Nerur, S. (Methods of Information in Medicine, 2008)
Objectives: The health information systems (HIS) field is characterized as being associated with health care and information systems. Drawing on several disciplines, a body of knowledge has come together that help define the core internal structure of the field. This study attempts to identify the emerging sub-fields using the bibliometric technique of author-cocitation analysis.Methods: Co-citation data for members of editorial boards of several health information systems journals for the period of 1998-2006 was collected and analyzed (N = 166). We performed numerous multivariate analyses, including cluster analysis, factor analysis and multidimensional scaling to extract the sub-fields.Results: Our findings indicate the presence of several strong sub-fields, including HIS evaluation, communication and e-health, and clinical DSS. In addition, we identified other sub-fields that are distinct but still emerging, such as adoption, outcome and policy, and use and impact of HIS. The study also confirms the existence of several historical sub-fields and contrasts technology-oriented sub-fields with managementoriented sub-fields. Topics on the periphery of HIS provide links to other disciplines as well.Conclusions: The study provides a unique perspective on the field of HIS, and the results indicate opportunities for further research that explores collaborations and social networks among the sub-fields.
Keywords: Author co-citation analysis (ACA); bibliometrics; field; health information system (HIS); sub-field